A Comprehensive Analysis of Augmented Reality Applications for Geometry Education: A Systematic Literature Review and Bibliometric Analysis - Muhammad, Ilham; Kusumah, Yaya Sukjaya; Turmudi, Turmudi; Elmawati, Elmawati; Maharani, Swasti (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2024)
This research represents a significant step in exploring the potential of Augmented Reality (AR) in the context of geometry learning. By utilizing the Scopus database, this research explores AR-related trends and content in geometry learning. The literature review method was used, with a bibliometric analysis approach and systematic literature review, which included four stages: identification, screening, eligibility, and inclusion, resulting in 31 final data. This is not just a description of the data but rather an attempt to present a deeper understanding of the role and potential of AR in enhancing geometry learning. In the ever-evolving world of education, a better understanding of the role of technology such as AR can open the door to more innovative and effective learning approaches. Research shows that AR technology can improve students' understanding of geometry concepts, increase learning motivation, and improve teachers' teaching skills. With AR applications, learning geometry becomes more interactive, visual, and engaging for students at various levels of education. In addition, the use of AR technology can also help create a more in-depth learning experience and motivate students to be more active in the learning process.